Implementasi Teknologi Dalam Perencanaan Karir Pada Era Digital : Peluang Dan Tantangan - Sintani, Priti; Arifa Nurlianti; Sartika (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This research examines how technology is implemented in career planning in the digital era by examining the opportunities and challenges. The implementation of technology in career planning in the digital era offers significant opportunities and challenges. In the digital era, technology has become an integral part in various aspects of life, including career planning. Technology can help individuals make more precise and effective decisions in planning their careers. However, the implementation of technology can also pose challenges such as how technology can be used effectively and how individuals can utilize technology to improve the quality of their lives and careers. The aim of this research is to determine and analyze the opportunities and challenges of implementing technology in career planning in the digital era. The research method carried out by this researcher uses a qualitative approach with descriptive methods. Data collection techniques were carried out using literature study techniques referring to several sources such as journals and other literature reviews. The results of this research show that technology can help individuals make more precise and effective decisions in planning their careers. However, the implementation of technology can also pose challenges, such as how technology can be used effectively and how individuals can utilize technology to improve the quality of their lives and careers.